Explaining the persistence of hazardous chemicals in the Doce River (Brazil) by multiple sources of contamination and a major environmental disaster - Yamamoto, F. Y. [UNESP]; Pauly, G. F.E. [UNESP]; Nascimento, L. S.; Fernandes, G. M.; Santos, M. P.; Figueira, R. C.L.; Cavalcante, R. M.; Grassi, M. T.; Abessa, D. M.S. [UNESP] (Elsevier, 2023)
High concentrations of hazardous chemicals may be introduced into aquatic ecosystems during episodes of acute and chronic environmental contamination. This study aimed to quantify inorganic and organic contaminants along the Doce River Basin (DRB), evaluate spatial and temporal variations of their concentrations, and their associations with the respective potential anthropogenic sources, considering the cumulative effects of a tailing dam rupture event. Multivariate analysis indicated that higher levels of trace elements in the Upper DRB were related to its proximity to the mining activities in this region, while organic contaminants such as PAHs are probably introduced by industrial effluents and urban centers along the DRB. In addition, seasonal variation showed to be an important factor influencing the distribution of chemicals, with wet season increasing levels of trace elements in the water. Despite the contribution of natural geological features in the Upper DRB, it becomes clearer that intense mineral exploitation for decades, combined with the dam failure disaster are responsible for the increased levels and spread of these inorganic contaminants along the DRB. Furthermore, other sources of organic contaminants contribute to this contamination scenario, resulting in complex mixtures of chemicals and increasing the ecological risks in the region.
Keywords: Complex mixtures; Geochemistry; Multivariate analysis; Organic chemicals; Trace elements